2014
DOI: 10.1136/bmjopen-2013-003824
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle protein levels are related to brain atrophy and cerebral white matter lesions in patients with manifest vascular disease: the SMART-MR study

Abstract: ObjectivesExtracellular vesicles (EVs) and their protein levels have been identified as a potential risk marker for the development of vascular disease. In the present study, we assessed whether levels of four previously identified EV proteins (cystatin C, serpin G1, serpin F2 and CD14) are associated with cerebral white matter lesions (WMLs) and brain atrophy.DesignCohort study; cross-sectional and prospective.SettingSingle centre, secondary and tertiary setting.Participants1309 patients with manifest vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Evidence has revealed that cystatin C binds to β-amyloid, resulting in the inhibition of β-amyloid deposition in senile plaques of AD (Sastre et al, 2004;Kaeser et al, 2007;Kanhai et al, 2014).…”
Section: Cystatin Cmentioning
confidence: 99%
“…Evidence has revealed that cystatin C binds to β-amyloid, resulting in the inhibition of β-amyloid deposition in senile plaques of AD (Sastre et al, 2004;Kaeser et al, 2007;Kanhai et al, 2014).…”
Section: Cystatin Cmentioning
confidence: 99%
“…Following translocation to ECs through exosome internalization, miR-132 regulates the expression of vascular ECs cadherin (VE-cadherin), an important adherens junction protein, by directly targeting eukaryotic elongation factor 2 kinase [31]. In addition, two proteins found in peripherally circulating plasma EVs, cystatin C and CD14, have been linked to the development of brain atrophy and to cerebral white matter lesions, a small vessel disease within the brain [32]. Because exosomes contain transferrin and insulin receptor [25,28], which mediate macromolecular passing through the blood-brain barrier (BBB), peripherally infused modified exosomes containing specific RNA were used to knockdown a specific gene in mouse brain [32][33][34].…”
Section: Biological Content Of Extracellular Vesiclesmentioning
confidence: 99%
“…In addition, two proteins found in peripherally circulating plasma EVs, cystatin C and CD14, have been linked to the development of brain atrophy and to cerebral white matter lesions, a small vessel disease within the brain [32]. Because exosomes contain transferrin and insulin receptor [25,28], which mediate macromolecular passing through the blood-brain barrier (BBB), peripherally infused modified exosomes containing specific RNA were used to knockdown a specific gene in mouse brain [32][33][34]. Considering the extraordinary intricate cytoarchitecture of the brain, the presence of EVs in the adult brain is hard to be documented.…”
Section: Biological Content Of Extracellular Vesiclesmentioning
confidence: 99%
See 2 more Smart Citations